EXPLORING VISUAL PROBABILISTIC REASONING: A QUALITATIVE STUDY ON JUNIOR HIGH SCHOOL STUDENTS’ PROBLEM-SOLVING IN PROBABILITY - Ashari, Nur Wahidin (Pedagogy: Jurnal Pendidikan Matematika, 2025)
Understanding students' probabilistic reasoning is crucial in developing effective instructional strategies for probability learning, as probability concepts often pose challenges for many students. This study employs a qualitative descriptive research design to explore the probabilistic reasoning processes of junior high school students in solving probability problems. The research focuses on three selected students who exhibit varying levels of reasoning ability. Data were gathered through think-aloud protocols, in-depth interviews, and analysis of students' written task worksheets. The think-aloud method allowed capturing students' cognitive processes during problem-solving, while interviews provided further insight into their reasoning patterns. Worksheets were used to confirm the accuracy and completeness of their solutions. Data analysis involved systematic coding and thematic categorization based on three key probabilistic reasoning indicators: Identifying, Conjecturing, and Constructing. Triangulation of multiple data sources enhanced the credibility and validity of the findings. The results reveal that students predominantly use visual probabilistic reasoning, especially through factor tree representations, and fulfill all three reasoning indicators. This study underscores the need for varied teaching approaches to improve students' conceptual understanding and flexible application of probability concepts in mathematics education.